Modern project finance : a casebook - Esty, Benjamin C. ([New York] : Wiley, 2004)
This book is an outstanding introduction to the field of project finance that explores why companies use project finance, why bankers engage it, and in analysing project capital structures, how project loans should be priced, and why some projects fail.
Includes bibliographical references (p. 508-518) and index
rua 02/12/13
Loans
Keywords: Capital investments; Economic development projects -- Finance; Industrial development projects -- Finance; Infrastructure (Economics) -- Finance; Project management -- Finance; Corporations -- Finance